Evaluation of Nurses’ Intervention toward Oral Hygiene in Critical Care Unit Patient at Baghdad City - Alaa Jawad Kadhim, Khalida Mohammed Khudur (Drugs and Cell Therapies in Hematology, 2021)
Oral hygiene care is the basis of health. Healthy people are able to meet their hygiene needs, while sick and elderly people with a physical handicap need people to help them with some needs. Objectives:This study aimed to evaluate of Nurses’ intervention toward Oral Hygiene in Critical Care Unit Patient Methodology:This is pre-experimental design was conducted on nurses who working in critical care unit at Baghdad city. started from the 15 of march 2020 to the April 15, 2021. probability of 30 nurses which consisted of two parts: the study sample’s sociodemographic characteristics for (10) items, Nurses’ intervention form was composed of (50) Items. Statistical Package for Social Sciences version 20.0 used to analyze the data. Results:The results of the current study showed that there was a statistically significantdifference in the mean of the study sample’s pertest and post-test, whichreveal that there was a significant improvement in their interventions toward Nursing Preparation before Starting Oral Hygiene forintensive care unit Patients and their interventions regarding Oral care for intensive care unit patient. Conclusions:The finding of the study reported that there wasimprovement in the results of the nurses’ interventions related to oral hygiene of comatose patients after implementation of the practices. Recommendation:The development aspect of the nurses‟ skills aftergraduation on a continuous periodic basis and they do not rely on theinformation and skills they learned from the study only. the hospital administration, maintenance work onthe aspects of intensive care to facilitate the implementation of nursingwork in terms of Oral hygiene and the provision of supplies and toolsfor oral hygiene.